Analisis Gradasi Bahan RAP Terhadap Nilai Kepadatan Dan CBR Menggunakan Rumus FULLER - Ardinata, Sofyan; , Ir. Sri Sunarjono, M.T, PhD; , Ir. Agus Riyanto, M.t (2016)
Roads are the infrastructure that used by society to improvet and stability of political, economic, social, cultural, defense and security. So in the development required careful planning and efficient. Issues of road damage that occurs pushing to make improvements and innovations. Utilization RAP (Reclaimed asphalt pavement) one of solution to overcome the problems of the road. The purpose of research that utilizes recycled materials in order to improve the quality of RAP with aggregate gradation change uses gradation Fuller so that it can be known how density and CBR value when compared to the original RAP.Research methods make improvements gradation RAP material that has been graded Fuller re-use formula to determine the density and CBR value that has been engineered RAP and RAP original gradation density values are then compared and CBR. Research conducted by inspection density, maximum density RAP original value of 1.55 g/cm3, the optimum water content 3.07%. RAP Fullerhas density 1.71 gr/cm3, the optimum water content of 8.4%. In testing the CBR, the CBR value obtained original RAP = 27%, RAP Fuller got value CBR = 60%. The final conclusion is that the RAP material which has been re-graded using the formula Fuller has a density and CBR value higher than the original RAP.